Bayezid Halife (er-Rûmî) ve Fatiha tefsiri (edisyon kritiği) secencelü’l ervah ve nukûşu’l elvâh - Özmen, Kerim (My University, 2003)
In my thesis which is called Bayezid Halife and His Exegesis of the Chapter of Fatiha which is called Secencelul Ervah Ve Nukuşül Elvah I studied the life and works of Bayezid Halife and the exegises he wrote on the chapter of Fatiha. The introduction contains a about the research, Sura and exegesis of Suras, the Sura of Fatiha and its interpretations. The first chapter, consists of the era in which Bayezid Halife lived, his life, his charesteristics, his teachers, his halifas and works. In the second chapter, Bayezid Halifa's exegises of Fatiha is introduced and examined. Afterwords the text of Secencelul Ervah Ve Nukuşül Elvah is given in Arabic. Bâyezid Halife (er- Rûmî) ve Fatiha Tefsiri Secencelü'l- Ervâh ve Nukûşu'l- Elvâh isimli tezimizde, Bâyezid Halife ve Fatiha Sûresine yazdığı tefsiri üzerinde durmaktayız. Giriş Bölümünde, araştırma hakkında genel bilgi, Sûre, Sûre Tefsirleri, Fatiha Sûresi ve tefsirleri gibi konular yer almaktadır. Birinci Bölümde ise Bâyezid Halife'nin yaşadığı dönem, hayatı, şahsiyeti, hocaları, halifeleri ve eserleri hakkında bilgi verilmiştir. İkinci Bölüme gelince burada, Bayezid Halife'nin Fatiha Tefsiri'nin tanıtım ve değerlendirilmesi yapılmıştır. Bu bölümden sonra ise, Fatiha Tefsiri'nin hazırladığımız Arapça metin kısmı gelmektedir.
Keywords: Tefsir